A green extraction strategy for the detection of antioxidants in food simulants and beverages migrated from plastic packaging materials. (16th April 2023) - Zhu, Wenjuan; Jin, Pingning; Yang, Hongrui; Li, Fei; Wang, Chen; Li, Tiemei; Fan, Jing
Graphical abstract: Highlights: A green method is proposed for detecting the migration levels of antioxidants. In-situ formation of DES and the extraction process have been completed in one step. The extraction reaches equilibrium rapidly without using volatile compounds. The established method shows high efficiency and strong anti-interference ability. The method can be used to detect antioxidants in food simulants and beverages. Abstract: Antioxidants, widely utilized in the food packaging field, have a risk of migrating into foodstuffs and eventually entering the human body. In this work, a novel method was established for green extraction and determination of antioxidants in food simulants migrated from plastic packaging materials. It was found that the antioxidants could be extracted directly from food simulants by in-situ formation of hydrophobic deep eutectic solvents with low toxic medium-chain fatty alcohols. Under the optimal conditions, the limit of detection was 0.15 to 0.25 µg/L, and the limit of quantification was 0.5 to 1.0 µg/L for the antioxidants. The extraction reaches equilibrium in 2 min. Importantly, butylated hydroxytoluene was detected in two types of the surveyed food contact materials. The established method shows high sensitivity, high enrichment factor, and strong anti-interference ability, and can be used for the separation and enrichment of ultra-trace antioxidants in foodstuffs.